Meropenem-Vaborbactam vs. Best Available Therapy for Carbapenem-Resistant Enterobacteriaceae Infections in TANGO II: Outcomes in Immunocompromised Patients. (4th October 2017) - Paterson, David L; Kwak, Eun J; Bhowmick, Tanaya; Alexander, Elizabeth; Loutit, Jeffrey S; Zhang, Shu; Dudley, Michael N; Walsh, Thomas J
Abstract: Background: Immunocompromised patients are at high risk for mortality due to carbapenem-resistant Enterobacteriaceae (CRE). Meropenem-vaborbactam (M-V) is a novel cyclic boronic acid β-lactamase inhibitor combination being developed for treatment of serious gram-negative infections, including CRE. This analysis reports outcomes among immunocompromised subjects in TANGO II, a randomized, open-label comparative trial with best available therapy (BAT) in subjects with complicated urinary tract infection (cUTI), acute pyelonephritis (AP), HABP/VABP, bacteremia, and cIAI, due to known or suspected CRE. Methods: Eligible subjects were randomized 2:1 to M-V (2g/2g every 8h) or BAT for 7 to 14 days. BAT included any of the following, alone or in combination: carbapenems, aminoglycosides, polymyxin B, colistin, tigecycline, or ceftazidime-avibactam (monotherapy only). Clinical cure was defined as complete resolution of signs or symptoms such that no further antimicrobial therapy was required. Results: Of the 50 subjects who had a baseline pathogen (m-MITT population), 19 (38.0%) were immunocompromised (4 leukemia/lymphoma, 5 medication, 10 transplant). Among the 43 subjects with a baseline CRE pathogen (mCRE-MITT), 18 (41.9%) were immunocompromised. The most common infection types among immunocompromised subjects (mCRE-MITT) were bacteremia (61.1%), cUTI/AP (16.7%), HABP/VABP (11.1%), and cIAI (11.1%). Clinical efficacy and mortality among immunocompromised in the mCRE-MITT population are shown. M-V was associated with fewer drug-related adverse events (30.8% vs. 40.0%), serious adverse events (38.5% vs. 50.0%), and renal-related adverse events (7.7% vs. 40.0%) than BAT. Conclusion: In immunocompromised subjects, receipt of M-V was associated with higher clinical cure rates and a lower mortality rate than BAT (m-MITT, mCRE-MITT populations). M-V is a promising treatment option for CRE in this population. Disclosures: D. L. Paterson, Achaogen: Consultant, Consulting fee; Merck: Consultant and Investigator, Consulting fee and Research grant; Shionogi: Consultant, Consulting fee; GlaxoSmithKline: Consultant, Consulting fee; E. Alexander, The Medicines Company: Shareholder, Salary; J. S. Loutit, The Medicine's Company: Employee and Shareholder, Salary; S. Zhang, The Medicines Company: Shareholder, Salary; M. N. Dudley, The Medicine's Company: Employee and Shareholder, Salary; T. J. Walsh, The Medicines Company: Consultant and Investigator, Consulting fee and Research grant; Astellas: Consultant and Investigator, Consulting fee and Research grant; Allergan: Consultant and Investigator, Consulting fee and Research grant; Merck: Consultant and Investigator, Consulting fee and Research grant